2020
DOI: 10.1212/wnl.0000000000008739
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration, midday napping, and sleep quality and incident stroke

Abstract: ObjectiveTo investigate the associations of sleep duration, midday napping, sleep quality, and change in sleep duration with risk of incident stroke and stroke subtypes.MethodsAmong 31,750 participants aged 61.7 years on average at baseline from the Dongfeng-Tongji cohort, we used Cox regression models to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for incident stroke.ResultsCompared with sleeping 7 to <8 hours/night, those reporting longer sleep duration (≥9 hours/night) had a greater r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
100
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 38 publications
8
100
2
1
Order By: Relevance
“…Findings of our cohort study are consistent with other observational studies 4 , 6 , 7 , 21 and demonstrate an increased risk of total stroke and ischemic stroke associated with long sleep, though the association was rather weak. However, our MR analyses did not confirm the observational findings which may indicate that residual confounding (eg, from chronic health conditions, such as obesity or obstructive sleep apnea) may have biased the results of observational studies.…”
Section: Discussionsupporting
confidence: 92%
“…Findings of our cohort study are consistent with other observational studies 4 , 6 , 7 , 21 and demonstrate an increased risk of total stroke and ischemic stroke associated with long sleep, though the association was rather weak. However, our MR analyses did not confirm the observational findings which may indicate that residual confounding (eg, from chronic health conditions, such as obesity or obstructive sleep apnea) may have biased the results of observational studies.…”
Section: Discussionsupporting
confidence: 92%
“…As the rst study to explore association between napping and HUA in Chinese rural adults, we also further found the joint effect of snoring frequency and napping duration on HUA. Some previous study had found the combined effect of napping or sleep quality and night sleep duration on some metabolic diseases [15,35]. Similarly, in the current study, we observed that habitual snoring (≥ 3 days/week) combined with longer daytime napping (≥ 61 min) increased 63% risk of HUA in total participants (66% for men and 63% for men), though no signi cant joint effects of snoring frequency and night sleep duration or daytime napping and night sleep duration existed.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also observed that daytime napping was independently associated with increased SUA level and risk of HUA. Many studies have reported that daytime napping or sleep duration was associated with metabolic diseases [12][13][14][15]. But few studies have evaluated the relationship of sleep variables such as daytime napping and night sleep duration with HUA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations